Neurodawn: An EEG-Based Non-Invasive Neuromodulation Prototype for Parkinson’s Disease - Rayyan Athaillah Muntazhar; Muhammad Azzam Alfarabi; Afryansyah Afryansyah (Universitas Islam Negeri Sumatera Utara, 2025)
Parkinson’s disease (PD) is a chronic neurodegenerative disorder that significantly affects patients’ quality of life, thereby necessitating safe, adaptive, and accessible intervention approaches. This study aims to develop Neurodawn, an electroencephalography (EEG)-based non-invasive neuromodulation prototype as a health technology innovation to support Parkinson’s disease management while strengthening a holistic approach aligned with ethical principles and humanistic values. The research employs a research and development (R&D) method, encompassing stages of system design, EEG device integration, signal processing, and initial performance evaluation of the prototype. The innovation of Neurodawn lies in the utilization of EEG signals as the foundation for developing a non-invasive neuromodulation system designed to minimize clinical risks and enhance user comfort. Beyond technical aspects, this study emphasizes key health ethics principles, including non-maleficence, beneficence, patient autonomy, equity in access to healthcare services, and the protection of neurophysiological data privacy as integral components of technology ethics. The spiritual perspective is understood as strengthening patient resilience through meaning, hope, and social support in coping with chronic illness. The development results indicate that Neurodawn can be implemented as a functional prototype and has the potential to be further developed as a supportive non-invasive intervention technology for patients with Parkinson’s disease. The integration of science, ethics, and spirituality forms the foundation to ensure that this innovation is both beneficial and dignified.